Sistem Informasi Akuntansi pada PT. Jape Dilijaya - David Sugiarto; Adi Wibowo (Jurnal Infra, 2017)
A drinking water company PT. Jape dilijaya still use manual process. Processes and data which recorded on the paper have a greater chance of getting mistakes or less integrated data than computerized process. Manager also hard to supervise data movement because the system still use non-integrated method to record data.Based on the background, therefore web-based accounting information system were developed to make easier supervision process anywhere, and anytime. Data that get inserted into the database can be more integrated, and prevent data loss because of non-integrated system. Steps to making the program start with analyzing current manual process on company and also the roles and jobs of every staff at the company. Step continued by designing Data flow diagram and entity relationship diagram. Next step is designing website interface using PHP a programming language and make a database using mysql.Program implemented can give many result including data maintenance of  PO, receiving account, purchase return , SO, inovice, sales return, BOM, work order, proof of using stock, Daily production report, proof of broken product, proof of broken stock, proof of cash used, proof of  bank used, proof of cash received, proof of bank received, general entries,  COA,  master database. Program generate reports including cards, registers, report of recievable details, report of payable details, report of goods mutation,  trial balance, income statement, balance sheet, Legder